Peranan Filsafat Ilmu terhadap Fisioterapi - Suwarni, Sri; Ediyono, Suryo (Journal of Health and Therapy, 2023)
Writing this article aims to know and understand what philosophy is about, its role in the science of Physiotherapy. Philosophy of science has an important role in physiotherapy services. In order to apply what is contained in the philosophy of science, it must be understood and focused on the understanding of human health and illness. For the development of physiotherapy science, research is needed with the right method as an effort to empirically prove the usefulness of a physiotherapy technology. The research results can be applied in physiotherapy services so that physiotherapy technology is based on evidence that has been proven empirically. Innovation as an effort to develop knowledge must continue to be carried out with research and the use of appropriate methods for the sake of benefit.